(untitled) (Fiep Bulletin - online, 2012)
This paper aims to correlate the physical activity and biochemical variables between employees of the University of Toledo Campus Paraná-PR. 60 employees were surveyed through interviews using the International Physical Activity Questionnaire and implementation of biochemical interest (glucose, uric acid, total cholesterol and triglycerides). It was found that 15 employees are very active, 22 are active, 21 are irregularly active and 2 are sedentary. Data were expressed as mean and standard deviation, and we noted the relationship between the level of physical activity and biochemical values ??obtained.